Implementation of Fammi Bi Syauqin in Strengthening the Memorization of PPTQ Al-Rasyid Students - Fitria, Laila Annis; Nurrohim, Ahmad; Faradiella, Elvynanda (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The use of the right method in memorizing the Quran is one of the most Russian things that need attention. The right method in memorizing the Quran can also be a benchmark for concern behind the quality of student reading. Through the family bi syauqin method, the author tries to develop a theory in presenting a new method for strengthening the memorization of the Quran for the students. Qualitative research seems sufficient to present the results of descriptive data in the form of oral and written words of people and behavior observed through interviews, observation, and documentation then analyzed with instructive models. With the hope, that the family bi syauqin method can help strengthen the memorization of the Quran in PPTQ Al Rasyid students.